The bat bugs (Hemiptera: Cimicidae) from Argentina: geographic distributions, hosts, and new records - Iorio, Osvaldo Di (Zootaxa, 2012)
Three species of bat bugs (Hemiptera: Cimicidae) are known from Argentina: Latrocimex spectans (Lent, 1941) [Corrientes] inthe subfamily Latrocimicinae Usinger, 1966; Cimex lectularius Linnaeus, 1758 [Jujuy; Salta; Tucumán; Catamarca; Chaco;Córdoba; Buenos Aires]; and Propicimex tucmatiani (Wygodzinsky, 1951) [Salta; Tucumán; Santiago del Estero], both in thesubfamily Cimicinae Latreille, 1802. The finding of bat bugs in the province of Buenos Aires extends 867.5 km southeast in a straight line the previous southermost locality given in Santiago del Estero province.